Filtered sunlight versus intensive electric powered phototherapy in moderate-to-severe neonatal hyperbilirubinaemia: a randomised controlled non-inferiority trial - Tina M Slusher, ProfMD; Hendrik J Vreman, PhD; Ann M Brearley, PhD; Yvonne E Vaucher, ProfMD; Ronald J Wong, BS; David K Stevenson, ProfMD; Olumide T Adeleke, MBBS; Ifelayo P Ojo, MPH; Grace Edowhorhu, FMLS; Troy C Lund, PhD; Daniel A Gbadero, MBBS (The Lancet Global Health, 2018)
Summary: Background: Kernicterus resulting from severe neonatal hyperbilirubinaemia is a leading cause of preventable deaths and disabilities in low-income and middle-income countries, partly because high-quality intensive phototherapy is unavailable. Previously, we showed that filtered-sunlight phototherapy (FSPT) was efficacious and safe for treatment of mild-to-moderate neonatal hyperbilirubinaemia. We aimed to extend these studies to infants with moderate-to-severe hyperbilirubinaemia. Methods: We did a prospective, randomised controlled non-inferiority trial in Ogbomoso, Nigeria—a simulated rural setting. Near-term or term infants aged 14 days or younger who were of 35 weeks or more gestational age and with total serum bilirubin concentrations at or above the recommended age-dependent treatment levels for high-risk neonates were randomly assigned (1:1) to either FSPT or intensive electric phototherapy (IEPT). Randomisation was computer-generated, and neither clinicians nor the parents or guardians of participants were masked to group allocation. FSPT was delivered in a transparent polycarbonate room lined with commercial tinting films that transmitted effective phototherapeutic light, blocked ultraviolet light, and reduced infrared radiation. The primary outcome was efficacy, which was based on assessable treatment days only (ie, those on which at least 4 h of phototherapy was delivered) and defined as a rate of increase in total serum bilirubin concentrations of less than 3·4 μmol/L/h in infants aged 72 h or younger, or a decrease in total serum bilirubin concentrations in those older than 72 h. Safety was defined as no sustained hypothermia, hyperthermia, dehydration, or sunburn and was based on all treatment days. Analysis was by intention to treat with a non-inferiority margin of 10%. Findings: Between July 31, 2015, and April 30, 2017, 174 neonates were enrolled and randomly assigned: 87 to FSPT and 87 to IEPT. Neonates in the FSPT group received 215 days of phototherapy, 82 (38%) of which were not assessable. Neonates in the IEPT group received 219 treatment days of phototherapy, 67 (31%) of which were not assessable. Median irradiance was 37·3 μW/cm2/nm (IQR 21·4–56·4) in the FSPT group and 50·4 μW/cm2/nm (44·5–66·2) in the IEPT group. FSPT was efficacious on 116 (87·2%) of 133 treatment days; IEPT was efficacious on 135 (88·8%) of 152 treatment days (mean difference −1·6%, 95% CI −9·9 to 6·7; p=0·8165). Because the CI did not extend below −10%, we concluded that FSPT was not inferior to IEPT. Treatment was safe for all neonates. Interpretation: FSPT is safe and no less efficacious than IEPT for treatment of moderate-to-severe neonatal hyperbilirubinaemia in near-term and term infants. Funding: Thrasher Research Fund and National Center for Advancing Translational Sciences.